Environmental sources of rapid growing nontuberculous mycobacteria causing disease in humans - van Ingen, J.; Boeree, M.J.; Dekhuijzen, P.N. R.; van Soolingen, D. (Clinical microbiology and infection, 2009)
Nontuberculous mycobacteria are environmental, opportunistic pathogens whose role in human disease is increasingly recognized, especially regarding the rapid growing mycobacteria (RGM). RGM are recovered from various environmental sources, both natural and man-made. In water systems, RGM can survive by forming biofilms and by interactions with protozoa. The presence and species diversity of RGM in water is influenced by temperature, pH and the chemical quality of the water, as well as the availability of nutrients, although the exact correlations remain controversial. Despite their omnipresence in environmental sources, the actual transmission of RGM to humans, with subsequent clinical disease, has rarely been proven. However, outbreaks as a result of contaminated water sources have been reported, although accidental presence in clinical samples cannot always be excluded. In this setting, the presence of RGM does not necessarily indicate a causal relationship with clinical disease; accidental presence in clinical samples cannot always be excluded. Future studies should focus on the exact environmental sources of infection, aiming to examine possibilities for prevention of infections in patients at risk. Furthermore, studies should focus on the actual sites of the active replication of RGM; their presence may not indicate their natural habitat.